2021
DOI: 10.1080/13645579.2021.1940774
|View full text |Cite
|
Sign up to set email alerts
|

Using Emojis and drawings in surveys to measure children’s attitudes to mathematics

Abstract: This article considers the implementation of Emojis as responses within survey research, measuring attitudes towards mathematics in children aged eight and nine years old. Participants answered two multi-item scales. The first required them to provide an Emoji to provide their responses to statements, whilst the second additionally required them to draw the Emoji they wished to use. The rationale was to allow children to feel more familiar with the common means of communication used in a 'digital era' in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…As the ages of the child participants ranged from five to twelve years, the guided survey tool needed to be brief and simple to accommodate all ages. A three-question survey was developed with two questions using an emotion scale of smiley faces as reported by previous studies [ 26 , 27 ] ( Figure 1 ). All but one child participant completed the program survey (n=30) over the three programs offered during the second year.…”
Section: Discussionmentioning
confidence: 99%
“…As the ages of the child participants ranged from five to twelve years, the guided survey tool needed to be brief and simple to accommodate all ages. A three-question survey was developed with two questions using an emotion scale of smiley faces as reported by previous studies [ 26 , 27 ] ( Figure 1 ). All but one child participant completed the program survey (n=30) over the three programs offered during the second year.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) comment that creative participatory research methods such as use of art are frequently considered “child-friendly”. Drawings are frequently used as a way to engage children in research (Günindi, 2015; Massey, 2022; Ogina and Nieuwenhuis, 2010; O'Connell, 2013). For example, Massey (2022) explored children's attitudes to mathematics, inviting participants aged eight and nine to draw emojis to communicate how they felt about this subject.…”
Section: Innovation In Qualitative Research: Use Of Drawingsmentioning
confidence: 99%
“…Drawings are frequently used as a way to engage children in research (Günindi, 2015; Massey, 2022; Ogina and Nieuwenhuis, 2010; O'Connell, 2013). For example, Massey (2022) explored children's attitudes to mathematics, inviting participants aged eight and nine to draw emojis to communicate how they felt about this subject. The authors concluded that this approach was an appropriate way to conduct survey research with younger children.…”
Section: Innovation In Qualitative Research: Use Of Drawingsmentioning
confidence: 99%
“…Selain itu, Skala Likert Beremoji (Emoji Likert Scale) digunakan untuk menambahbaikkan soal selidik ini. Hal ini kerana skala tersebut lebih sesuai, lebih mudah difahami, dan dapat menarik perhatian responden yang terdiri daripada kalangan murid sekolah rendah (Messy, 2021).…”
Section: Pengumpulan Dataunclassified